NF-κB regulates radioresistance mediated by β1-integrin in three-dimensional culture of breast cancer cells - Ahmed, Kazi Mokim (2013)
β1-integrin induction enhances breast cancer cell survival after exposure to ionizing radiation (IR), but the mechanisms of this effect remain unclear. Although NF-κB initiates prosurvival signaling pathways post-IR, the molecular function of NF-κB with other key elements in radioresistance, particularly with respect to extracellular matrix-induced signaling, is not known. We discovered a typical NF-κB binding site in the β1-integrin promoter region, indicating a possible regulatory role for NF-κB. Using 3-dimensional laminin-rich extracellular matrix (3D lrECM) culture, we show that NF-κB is required for β1-integrin transactivation in T4-2 breast cancer cells post-IR. Inhibition of NF-κB reduced clonogenic survival, and induced apoptosis and cytostasis in formed tumor colonies. In addition, T4-2 tumors with inhibition of NF-κB activity exhibit decreased growth in athymic mice, which was further reduced by IR with downregulated β1-integrin expression. Direct interactions between β1-integrin and NF-κB p65 were induced in non-malignant breast epithelial cells, but not in malignant cells, indicating context specific regulation. Since β1-integrin also activates NF-κB, our findings reveal a novel forward feedback pathway that could be targeted to enhance therapy.